The Roles of Prebiotics on Impaired Immune System in Preterm Infants: A Narrative Literature Review - Zakiudin Munasir (Amerta Nutrition, 2021)
ABSTRACT Background: After birth, preterm infants face numerous challenges, including short and long-term morbidities, to survive and grow well with impaired immune and gastrointestinal systems. According to data from 184 countries, preterm birth rate ranges from 5-18%, accounting for 35% of all new born deaths. Purpose: This literature review aimed to summarize the evidence for the impact of prematurity on immune system development and the benefit of prebiotics on gut microbiota and immune responses. Discussion: Various studies in this narrative literature review showed that preterm infants have both qualitative and quantitative immune response deficits compared to term infants. Preterm newborns also have impaired intestinal immunity, underdeveloped intestinal mucosa barrier, and gut dysbiosis, which predisposes them to life-threatening infections. Early balanced gut microbiota in infants believed to be essential for adequate intestinal physiological functions and immune system maturation. The use of prebiotics, including human milk oligosaccharides (HMOs) in human breast milk, has been found to decrease the risk of various infections and cognitive impairment. A previous study found that prebiotic oligosaccharides supplementation was well-tolerated, significantly increased Bifidobacteria growth, and reduced the presence of gut pathogens. Conclusions: There was robust evidence that breast milk and prebiotics supplementation may support the gut microbiome and immune system in preterm infants. However, different types of synthetic prebiotics offer different benefits, and the protective effect seems to depend on the supplementation duration and dosage.